Photosensitive composition, composite, electronic component, and method for producing electronic component
By using a photosensitive composition containing precious metal powder and a dispersant with high solubility parameters, the problem of difficult formation of thin wire structures in electronic devices is solved, and the effect of shortening development time and reducing inter-line residues is achieved, and productivity and finished products are improved. Rate.
Patent Information
- Application Number
- CN201910218453.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-03-23
- Filing Date
- 2019-03-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-06-05
AI Technical Summary
The prior art is difficult to stably form a thin wire structure of the conductive layer in an electronic device, resulting in an extended development time and the occurrence of inter-line residues, which affects productivity and yield.
A photosensitive composition containing a noble metal powder, a photopolymerizable compound, a photopolymerization initiator, and a dispersant with a solubility parameter higher than 9.9 is used to form a conductive layer through a photocuring and developing process.
Shorten the development time, reduce the occurrence of inter-line residues, improve productivity and yield, and ensure the thin wire structure and conductivity of the conductive layer.
Smart Images

Figure BDA0002002810570000191 
Figure BDA0002002810570000192 
Figure BDA0002002810570000221
Abstract
Description
Technical Field
[0001] The present invention relates to a photosensitive composition and its use, and more particularly to a photosensitive composition, a composite, an electronic component, and a method for producing the electronic component. Background Art
[0002] In the past, the following method is known: a conductive layer and a resin insulating layer are formed on a substrate by photocuring a photosensitive composition containing a photopolymerizable compound and a photopolymerization initiator (see Patent Documents 1 and 2). For example, Patent Document 1 discloses the following scheme: a conductive layer formed of a base metal is formed on a substrate by photolithography. In the above method, first, a photosensitive composition is applied to the substrate, dried, and formed into a film (film forming process). Then, a photomask having a predetermined opening pattern is covered on the above-formed film, and the film is exposed through the photomask (exposure process). Thus, the exposed portion of the film is photocured. Then, the unexposed portion that is shielded from light by the photomask is corroded and removed in an alkaline aqueous developer (development process). Then, the film that becomes the desired development pattern is baked (baking process). According to the photolithography method including the above process, a fine conductive layer can be formed compared with various previous printing methods.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent No. 3975932
[0006] Patent Document 2: Japanese Patent Application Publication No. 2015-161815 Summary of the invention
[0007] However, in recent years, the miniaturization and high performance of various electronic devices have been rapidly promoted, and the electronic components installed in the electronic devices are also required to be further miniaturized and high-densified. With this, the manufacturing of electronic components requires low resistance and thinning (narrowing) of the conductive layer. For example, it is required to form a conductive layer with a line width of 30μm / 30μm or less and a space between adjacent wirings (line and space: L / S) or less. 20μm / 20μm or less.
[0008] However, according to the research of the present inventors, when the viscosity of the photopolymerizable compound used is high, for example, when the photopolymerizable compound used is a polymer with a large molecular weight, it is difficult to stably form a conductive layer of thin lines with a small L / S. That is, if the viscosity of the photopolymerizable compound is high, the adhesion between the substrate and the unexposed portion becomes high. However, if the L / S is small, it becomes difficult to supply the developer to the space between the lines during the development process. As a result, the unexposed portion becomes difficult to remove, and the development time, that is, the time required to completely remove the unexposed portion (time until the development point (BP)) sometimes becomes longer. In addition, if Figure 2 As shown in the schematic diagram of FIG, the residue that is not completely removed by etching (hereinafter referred to as "inter-line residue") sometimes remains in the space. As a result, there is a problem of leakage current due to the tunnel effect, or short circuit failure due to the connection between wirings. Therefore, the user's requirement is to reduce the occurrence of inter-line residue while shortening the development time, and to improve productivity and yield.
[0009] The present invention is made in view of the above aspects, and its purpose is to provide: a photosensitive composition that can shorten the development time and reduce the occurrence of inter-line residues. In addition, another related purpose is to provide: a composite having a conductive film formed from a dried body of the photosensitive composition. In addition, another related purpose is to provide: an electronic component having a conductive layer formed from a calcined body of the photosensitive composition; and a method for producing the same.
[0010] According to the present invention, a photosensitive composition is provided, which comprises: a precious metal powder, a photopolymerizable compound, a photopolymerization initiator and a dispersant. The solubility parameter of the dispersant is 9.9 (cal / cm 3 ) 1 / 2 above.
[0011] The photosensitive composition contains a dispersant having a solubility parameter as high as 9.9 or more. As a result, the unexposed portion can be easily removed in the development process, and the development time can be shortened. In addition, the generation of residues between lines can be reduced, and a conductive layer of thin lines with a small L / S can be formed with good reproducibility. As a result, the productivity and yield rate can be improved.
[0012] In this specification, the term "solubility parameter (SP value)" refers to, for example, "Study on the solubility parameters of additives", Coatings Research, No. 152, pp41-46, October 2010, [online], <URL: http: / / www.kansai.co.jp / rd / token / pdf / 152 / 08.pdf >, measured by turbidity titration. The specific measurement method is described in the section of the examples. In addition, the unit of SP value is (cal / cm 3 )1 / 2 .
[0013] In a preferred embodiment disclosed herein, the photopolymerizable compound comprises a photopolymerizable polymer having a weight average molecular weight of 5000 or more. When the photopolymerizable compound comprises a photopolymerizable polymer, it is more difficult to remove the unexposed portion in the development step. Thus, the effect of the technology disclosed herein can be better exerted.
[0014] In a preferred embodiment disclosed herein, the photopolymerizable compound includes one or more compounds having an acidic group. This can further enhance the removability of the unexposed portion in the development step.
[0015] In a preferred embodiment disclosed herein, when the total amount of the noble metal powder is 100 parts by mass, the content ratio of the dispersant is 0.1 parts by mass or more and 2.7 parts by mass or less. Thus, the removability of the unexposed portion and the etching resistance of the exposed portion can be balanced at a high level. That is, the removability of the unexposed portion is improved in the development process, and for the exposed portion, high adhesion (tackiness) to the substrate can be achieved.
[0016] In a preferred embodiment disclosed herein, the above dispersant is composed only of a solubility parameter of 9.9 (cal / cm 3 ) 1 / 2 The above compound composition makes it more difficult for residues to remain between the wires, and the space portion of the thin wire can be ensured more stably.
[0017] In a preferred embodiment disclosed herein, the dispersant contains one or more compounds having an acidic group. Thus, in the development step, the unexposed portion can be removed more quickly and cleanly using an aqueous developer.
[0018] In a preferred embodiment disclosed herein, the noble metal powder includes silver-based particles, thereby achieving a conductive layer having an excellent balance between cost and low resistance.
[0019] According to the present invention, there is provided a composite body comprising: a green sheet; and a conductive film which is disposed on the green sheet and is formed from a dried product of the photosensitive composition.
[0020] In addition, according to the present invention, there is provided an electronic component comprising: a conductive layer formed from a calcined body of the above-mentioned photosensitive composition. According to the above-mentioned photosensitive composition, a conductive layer of thin lines with a small L / S can be formed with good reproducibility. Therefore, by using the above-mentioned photosensitive composition, an electronic component having a small and / or high-density conductive layer can be suitably realized.
[0021] In addition, according to the present invention, there is provided a method for manufacturing an electronic component, which comprises the following steps: applying the above-mentioned photosensitive composition to a substrate, exposing and developing, and then baking to form a conductive layer formed by a baked body of the above-mentioned photosensitive composition. By such a manufacturing method, electronic components with small and / or high-density conductive layers can be stably manufactured, and productivity and yield can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a cross-sectional view schematically showing the structure of a multilayer chip inductor according to one embodiment of the present invention.
[0023] Figure 2 A schematic diagram for explaining the residue between lines.
[0024] Description of Reference Numerals
[0025] 1 Multilayer Chip Inductor
[0026] 10 Main body
[0027] 12 Ceramic layer
[0028] 14 Internal electrode layer
[0029] 20 External electrodes DETAILED DESCRIPTION
[0030] The following is a description of suitable embodiments of the present invention. It should be noted that the necessary technical features required for the implementation of the present invention (such as the preparation method of the photosensitive composition, the formation method of the conductive film and the conductive layer, the manufacturing method of the electronic component, etc.) other than the features specifically mentioned in this specification (such as the composition of the photosensitive composition) can be understood based on the technical content taught in this specification and the general technical knowledge of those skilled in the art in this field. The present invention can be implemented based on the content disclosed in this specification and the technical knowledge in this field.
[0031] It should be noted that in the following description, a film-like body (dried product) obtained by drying the photosensitive composition at a temperature below the boiling point of the dispersant, specifically, at about 200° C. or below, for example, at 100° C. or below is referred to as a “conductive film”. The conductive film includes all the unfired (before firing) film-like bodies. The conductive film may be an uncured material before photocuring or a cured material after photocuring. In addition, in the following description, a sintered body (fired product) obtained by firing the photosensitive composition at a sintering temperature above the sintering temperature of the precious metal powder is referred to as a “conductive layer”. The conductive layer includes wiring (linear body), wiring pattern, and solid pattern.
[0032] In addition, the expression "A to B" which shows a range in this specification means A or more and B or less.
[0033] 《Photosensitive composition》
[0034] The photosensitive composition disclosed herein can be suitably used for the preparation of a layer formed of a noble metal, such as a conductive layer, a heat dissipation layer, etc. The photosensitive composition disclosed herein comprises: a noble metal powder, a photopolymerizable compound, a photopolymerization initiator, and a dispersant as essential components. The following describes each component in turn.
[0035] <Precious metal powder>
[0036] Precious metal powder is a component that imparts conductivity to a conductive layer obtained by, for example, calcining a photosensitive composition. As precious metal powder, there is no particular limitation, and one or more kinds can be suitably selected from conventionally known materials, for example, according to the purpose, etc., for use. As suitable examples of precious metal powder, single substances of metals such as gold (Au), silver (Ag), platinum (Pt), palladium (Pd), rhodium (Rh), iridium (Ir), ruthenium (Ru), osmium (Os), and mixtures thereof, alloys, etc. can be cited. As alloys, for example, silver alloys such as silver-palladium (Ag-Pd), silver-platinum (Ag-Pt), and silver-copper (Ag-Cu) can be cited.
[0037] In a suitable embodiment, the noble metal powder includes silver particles. Silver has a low cost and high electrical and thermal conductivity. Therefore, by including silver particles in the noble metal powder, a conductive layer having an excellent balance between cost and low resistance can be achieved, for example.
[0038] It should be noted that, in this specification, "silver-based particles" refer to all particles containing silver components. Examples of silver-based particles include single substance silver, the above-mentioned silver alloys, core-shell particles with silver-based particles as cores, such as silver-ceramic core-shell particles, etc.
[0039] There is no particular limitation on the D of the precious metal powder. 50 The particle size (the particle size corresponding to 50% of the cumulative value from the smaller particle size side in the volume-based particle size distribution based on the laser diffraction / scattering method) can be approximately 1 to 5 μm from the perspective of compatibility with the exposure performance in the exposure process. 50 The particle size is within the above range, so that the exposure performance of the exposed part can be improved, and thin lines can be formed more stably. From the viewpoint of suppressing aggregation in the photosensitive composition and improving stability, the D of the noble metal powder is preferably 50 The particle size may be, for example, 1.5 μm or more, or 2 μm or more. In addition, from the viewpoint of improving the fine line formability or promoting the densification and low resistance of the conductive layer, the D of the noble metal powder may be 2.5 μm or more. 50 The particle size may be, for example, 4.5 μm or less or 4 μm or less.
[0040] The noble metal powder may have an organic surface treatment agent attached to its surface. The organic surface treatment agent may be used for at least one of the following purposes, for example, to improve the dispersibility of the noble metal powder in the photosensitive composition, to improve the affinity of the noble metal powder with other components, and to prevent surface oxidation of the metal constituting the noble metal powder. Examples of the organic surface treatment agent include fatty acids such as carboxylic acids, and benzotriazole compounds.
[0041] There is no particular limitation, the ratio of the precious metal powder in the photosensitive composition as a whole is generally 50% by mass or more, typically 60 to 95% by mass, for example 70 to 90% by mass. By satisfying the above range, it is suitable for forming a conductive layer with excellent compactness and conductivity. In addition, the operability of the photosensitive composition and the workability when formed into a conductive film can be improved.
[0042] <Photopolymerizable Compound>
[0043] Photopolymerizable compounds are photocurable components that are cured by polymerization reactions, crosslinking reactions, etc., through active species generated by the decomposition of the photopolymerization initiator described later. The polymerization reaction can be, for example, addition polymerization or ring-opening polymerization. There are no particular limitations on the photopolymerizable compounds, and one or more kinds can be appropriately selected from conventionally known substances according to, for example, the purpose, the type of substrate, etc. Photopolymerizable compounds typically have one or more unsaturated bonds and / or cyclic structures. As a suitable example of a photopolymerizable compound, there can be cited free radical polymerizable compounds having one or more ethylenically unsaturated bonds such as (meth)acryloyl groups and vinyl groups, and cationic polymerizable compounds having a cyclic structure such as an epoxy group.
[0044] In this specification, the photopolymerizable compound includes a photopolymerizable monomer having a weight average molecular weight of less than 1500, a photopolymerizable oligomer having a weight average molecular weight of 1500 or more and less than 5000, and a photopolymerizable polymer having a weight average molecular weight of 5000 or more.
[0045] In addition, the "weight average molecular weight" in this specification means the weight-based average molecular weight obtained by measuring by gel chromatography (gel permeation chromatography: GPC) and converting using a standard polystyrene calibration curve.
[0046] In a suitable embodiment, the photopolymerizable compound contains a photopolymerizable polymer with a weight average molecular weight of 5000 or more. Compared with monomers and oligomers, photopolymerizable polymers can be cured with relatively less exposure. Therefore, it can be stably cured until the depth of the exposed part (the part close to the substrate). Therefore, by including a photopolymerizable polymer, the adhesion between the substrate and the conductive layer is improved, which can be suitable for suppressing the occurrence of undesirable conditions such as peeling and disconnection in the conductive layer. In addition, the water resistance and durability of the conductive layer can be improved. In addition, when the photopolymerizable compound contains a photopolymerizable polymer, the adhesion (tackiness) to the substrate is improved, and the removability of the unexposed part in the development process is reduced. Therefore, the application of the technology disclosed herein is effective. The weight average molecular weight of the photopolymerizable compound is approximately 10,000 or more, typically 15,000 or more, for example, 20,000 or more, and approximately 100,000 or less, for example, 50,000 or less. The photopolymerizable compound preferably further contains at least one of a photopolymerizable monomer and a photopolymerizable oligomer on the basis of the photopolymerizable polymer.
[0047] In a suitable embodiment, the photopolymerizable compound includes: a monomer having a (meth)acryloyl group, and a (meth)acrylate having the monomer as a structural unit. By including the (meth)acrylate in the photopolymerizable compound, the flexibility of the conductive layer and the followability to the substrate can be improved. As a result, the occurrence of undesirable conditions such as peeling and disconnection can be better suppressed. As a suitable example of (meth)acrylate, there can be cited: a homopolymer of an alkyl (meth)acrylate; a copolymer having an alkyl (meth)acrylate as a main monomer and containing a secondary monomer copolymerizable with the main monomer.
[0048] In addition, in this specification, "(meth)acryl" means a term including "methacryl" and "acryl", and "(meth)acrylate" means a term including "methacrylate" and "acrylate".
[0049] In a suitable embodiment, the double bond equivalent of the (meth)acrylate (calculated value as weight average molecular weight / number of C=C double bonds) is approximately 200 or more, typically 300 or more, for example 400 or more, and further 450 or more, and approximately 1000 or less, for example 500 or less. If the double bond equivalent is within the above range, the removability of the unexposed portion and the etching resistance of the exposed portion can be balanced at a high level in the development process. That is, the development time can be further shortened, and the occurrence of undesirable conditions such as peeling and disconnection can be more effectively suppressed.
[0050] In a suitable embodiment, the (meth)acrylate includes: a monomer having a (meth)acryloyl group and an ionic functional group (such as an acidic group) as a structural unit. As a result, the removability of the uncured portion is effectively improved, and the effect of the technology disclosed herein can be exerted at a higher level. As specific examples of (meth)acrylates having ionic functional groups in addition to the (meth)acryloyl group, for example, carboxyl-containing (meth)acrylates, phosphoric acid-containing (meth)acrylates, acid-modified epoxy (meth)acrylates, carboxyl-containing urethane-modified epoxy (meth)acrylates, etc. can be cited. Among them, preferably include: a monomer containing a (meth)acryloyl group and a carboxyl group, and a (meth)acrylate with the monomer as a structural unit. As commercially available products of such (meth)acrylates, for example, CYCLOMER P (trademark) ACA Z200M, Z230AA, Z250, Z251, Z300, Z320, and Z254F manufactured by Daicel Ornex Co., Ltd. can be cited.
[0051] In a suitable embodiment, the photopolymerizable compound includes: a photopolymerizable compound (a compound containing a carbamate bond) having a carbamate bond (-NH-C(=O)-O-). For example, the above-mentioned photopolymerizable polymer can be a carbamate bond-containing polymer having a carbamate bond, or, on the basis of the above-mentioned photopolymerizable polymer, it further includes a carbamate bond-containing monomer having a carbamate bond, and a carbamate bond-containing oligomer having a carbamate bond. By including a carbamate bond-containing compound in the photopolymerizable compound, the etching resistance of the exposed part can be better improved, and a conductive layer with better flexibility and stretchability can be achieved. Therefore, the adhesion between the substrate and the conductive layer can be improved, so as to suppress the occurrence of undesirable situations such as peeling and disconnection at a high level. As a suitable example of a compound containing a carbamate bond, carbamate-modified (meth)acrylate, carbamate-modified epoxy, etc. can be cited.
[0052] In one suitable embodiment, the photopolymerizable compound includes: a compound having an acidic group. For example, it includes a compound having a resin acid value of approximately 30 mgKOH / g or more, typically 50 mgKOH / g or more, for example 100 to 150 mgKOH / g. Moreover, the resin acid value of the photopolymerizable compound as a whole is preferably within the above range. In other words, the photopolymerizable compound as a whole preferably exhibits a specified acidity. If the resin acid value is above the specified value, the unexposed portion can be removed more quickly and cleanly using an aqueous developer in the development process. In addition, if the resin acid value is below the specified value, the solubility in the aqueous developer is suppressed in the development process, and peeling and disconnection of the exposed portion can be better suppressed.
[0053] In addition, the "acid value" in this specification refers to the content (mg) of potassium hydroxide (KOH) required to neutralize the free fatty acids contained in a unit sample (1g). The unit is mgKOH / g.
[0054] In a preferred embodiment, the SP value of the photopolymerizable compound is approximately 20 (cal / cm 3 ) 1 / 2 Within, typically 8 to 13 (cal / cm 3 ) 1 / 2 For example, it can be 10 to 13 (cal / cm 3 ) 1 / 2 It should be noted that, when multiple compounds are used as photopolymerizable compounds, the value (weighted average) obtained by calculating the product of the SP value of each compound and the composition ratio of each compound is used as the SP value of the photopolymerizable compound. In this way, the overall stability of the photosensitive composition can be improved, and the effect of the technology disclosed herein can be exerted at a higher level.
[0055] In another suitable embodiment, the glass transition temperature (Tg value based on differential scanning calorimetry (DSC)) of the photopolymerizable compound is approximately above 40°C, typically above 50°C, for example above 60°C, and further above 100°C, and in one example above 120°C, above 130°C, and approximately below 200°C, for example below 150°C. As a result, the flexibility and adhesion of the conductive film can be further improved, and the adhesion between the substrate and the conductive layer can be further improved. In addition, when the Tg value is within the above range, the adhesion (viscosity) to the substrate is improved, and the removability of the unexposed portion in the development process is reduced. Therefore, the application of the technology disclosed herein is effective.
[0056] Without particular limitation, when the photopolymerizable compound includes a photopolymerizable polymer, the ratio of the photopolymerizable polymer to the entire photopolymerizable compound is, by mass, approximately 10% or more, typically 20% or more, for example, 30% or more, approximately 90% or less, typically 80% or less, for example, 50% or less. When the above range is met, the effect of the technology disclosed herein can be exerted at a high level. In addition, without particular limitation, when the photopolymerizable compound includes at least one of a photopolymerizable monomer and a photopolymerizable oligomer, the ratio of at least one of the photopolymerizable monomer and the photopolymerizable oligomer to the entire photopolymerizable compound is, by mass, approximately 10% or more, typically 20% or more, for example, 50% or more, approximately 90% or less, typically 80% or less, for example, 70% or less.
[0057] There is no particular limitation, and the ratio of the photopolymerizable compound in the photosensitive composition as a whole is approximately 0.1 to 50 mass%, typically 0.5 to 30 mass%, for example, 1 to 20 mass%, and further 5 to 15 mass%. In addition, there is no particular limitation, and the ratio of the photopolymerizable compound contained is approximately 0.1 to 50 mass parts, typically 0.5 to 30 mass parts, for example, 1 to 20 mass parts relative to 100 mass parts of precious metal powder. By satisfying the above range, it is suitable to exert the photocurability of the photosensitive composition, and the conductive layer can be stably formed at a high level.
[0058] <Photopolymerization Initiator>
[0059] The photopolymerization initiator is a component that decomposes by irradiating active energy rays such as visible light, ultraviolet light, and electron beams, generates active species such as free radicals and cations, and initiates the reaction of photopolymerizable compounds. As a photopolymerization initiator, one or more kinds can be appropriately selected from the previously known substances according to the type of photosensitive resin. As a suitable example, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butane-1-one, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4-diethylthioxanthone, benzophenone, etc. can be cited.
[0060] The ratio of the photopolymerization initiator in the total photosensitive composition is not particularly limited, but is generally 0.01 to 5% by mass, typically 0.1 to 3% by mass, for example 0.2 to 2% by mass. This allows the photocurability of the photosensitive composition to be suitably exerted, and a conductive layer can be formed more stably.
[0061] <Dispersant>
[0062] The dispersant is an essential component for improving the removability of the unexposed portion in the development process. In the technology disclosed herein, the SP value of the dispersant based on the turbidity titration method is 9.9 (cal / cm 3 ) 1 / 2 The above. It should be noted that, when using multiple compounds as dispersants, the value (weighted average) obtained by calculating the product of the SP value of each compound and the composition ratio of each compound is used as the SP value of the dispersant. The SP value is a scale that represents the degree of hydrophilicity and hydrophobicity. By making the SP value greater than the specified value, the "compatibility" between the aqueous developer and the photosensitive composition becomes better. More specifically, the interaction between the resin component (such as a photopolymerizable compound, an organic binder described later) and the precious metal powder can be reduced, and the resin component and the precious metal powder become easily soluble in the aqueous developer. As a result, the removability of the unexposed portion can be appropriately improved.
[0063] The SP value is 9.9 (cal / cm 3 ) 1 / 2 Commercial products of the above dispersants include, for example, Malialim (trademark) SC1015F manufactured by Daicel Ornex Co., Ltd., and Hypermer (trademark) KD-4, KD-8, and KD-9 manufactured by Croda Japan Ltd. From the viewpoint of low cost and the viewpoint of achieving the above effects with a smaller usage amount, the SP value of the dispersant is 10.0 (cal / cm 3 ) 1 / 2 Above, for example, it can be 10.4 (cal / cm 3 ) 1 / 2 In addition, the upper limit of the SP value of the dispersant is not particularly limited, but is generally 30 (cal / cm 3 ) 1 / 2 Below, for example, 20 (cal / cm 3 ) 1 / 2 Below, in one example, it can be 15 (cal / cm 3 ) 1 / 2 the following.
[0064] As long as the dispersant satisfies the above-mentioned range of SP value, one or more kinds of compounds known to be used as dispersants in this process can be appropriately selected for use, for example, according to the types of precious metal powder and photopolymerizable compounds. In a suitable scheme, the dispersant contains one or more compounds with acidic groups. The acidic group is a substituent with a dissociable proton and acidic in water. Among them, it is preferred to include: compounds with functional groups that reflect relatively high acidity, such as phenolic hydroxyl, carboxyl, sulfonic, phosphonyl, boric acid, etc. The acidic group has a strong coordination to the precious metal particles constituting the precious metal powder. Therefore, by using a compound with an acidic group, the interaction between the acidic group of the photopolymerizable polymer and the precious metal particles is weakened, and the photopolymerizable polymer becomes easily soluble in the developer. As a result, the removability of the unexposed part can be improved more well.
[0065] The compound having an acidic group preferably has an acid value. That is, it is an acidic compound having an acid value of more than the detection lower limit (depending on the measurement accuracy, but generally more than 0.5 mgKOH / g). The acid value of the compound having an acidic group is generally more than 10 to 200 mgKOH / g, for example, it can be 20 to 100 mgKOH / g. Thus, the effect of the technology disclosed herein can be exerted at a higher level. In addition, the compound having an acidic group can further have a basic group. That is, it can be an amphoteric compound. In the above case, the compound having an acidic group may not have an acid value.
[0066] The structure of one or more compounds constituting the dispersant is not particularly limited, and typically has: a linear straight chain type, or a branched structure in which a plurality of side chains (carbon chains branching from the main chain. The same below. For example, graft chains) are bonded to a linear main skeleton (carbon chain with the largest number of carbons. The same below.). Alternatively, it can be a comb-type structure in which a plurality of side chains are arranged along the main skeleton. At least one of the main skeleton and the plurality of side chains may have an ionic functional group. The ionic functional group may be present in the main skeleton, or at the end or in the middle of the side chain. However, the main skeleton and / or the plurality of side chains may also be hydrophobic without an ionic functional group. The main skeleton may have: polyfunctionality with a plurality of ionic functional groups. The main skeleton may, for example, be a polycarboxylic acid having a plurality of the above-mentioned acidic groups, a polyamine having a plurality of basic groups, and the like. The side chain may be an alkylene chain, a polyoxyalkylene chain, such as an ethylene oxide (EO) chain, or a propylene oxide (PO) chain. The side chain may be a saturated or unsaturated, linear or branched hydrocarbon chain.
[0067] The weight average molecular weight of each of the one or more compounds constituting the dispersant is approximately 100 or more, typically 500 or more, for example 1000 or more, and approximately 100,000 or less, typically 50,000 or less, for example 30,000 or less. By setting the above range, the coordination to micron-sized noble metal particles can be improved. In addition, the viscosity of the photosensitive composition can be suppressed, and the removability of the unexposed portion can be improved more effectively. Therefore, the effect of the technology disclosed herein can be exerted at a higher level.
[0068] In dispersants, the solubility parameter can be lower than 9.9 (cal / cm 3 ) 1 / 2 For example, the solubility parameter is lower than 9.9 (cal / cm 3 ) 1 / 2 The content ratio of the compound can be less than about 50 mass % of the total compound constituting the dispersant, preferably less than 40 mass %, more preferably less than 10 mass %, and particularly preferably no solubility parameter less than 9.9 (cal / cm 3 ) 1 / 2 In other words, it is particularly preferred that the dispersant consists only of a compound having a solubility parameter of 9.9 (cal / cm 3 ) 1 / 2 The above compounds are formed. As a result, the residue between the wires is less likely to remain in the space, and the thin wires can be formed more stably. That is, the thin wire formability can be improved more well. Therefore, the effect of the technology disclosed herein can be exerted at a higher level.
[0069] In a preferred embodiment, the absolute value of the difference between the SP values of water and the dispersant, that is, |SP value of water - SP value of dispersant| is approximately 13.6 (cal / cm 3 ) 1 / 2 Within, typically 13.5 (cal / cm 3 ) 1 / 2 Within, for example, 13.1 (cal / cm 3 ) 1 / 2 Thereby, the affinity with the aqueous developer can be further improved, and the removability of the unexposed portion can be improved more effectively.
[0070] In another preferred embodiment, the absolute value of the difference between the SP values of the photopolymerizable compound and the dispersant, that is, |SP value of the photopolymerizable compound - SP value of the dispersant| is approximately 13 (cal / cm 3 ) 1 / 2 Within, typically 10 (cal / cm 3 ) 1 / 2 Within, for example, 8 (cal / cm 3 ) 1 / 2In one example, it can be 5 (cal / cm 3 ) 1 / 2 Thereby, the stability of the entire photosensitive composition can be improved, and the effect of the technology disclosed herein can be exerted at a higher level.
[0071] There is no particular limitation, and the ratio of the dispersant in the photosensitive composition as a whole is approximately 0.01 to 5% by mass, typically 0.1 to 3% by mass, for example, 0.2 to 2% by mass. As a result, it is easier to remove the unexposed portion in the development process, and the occurrence of inter-wire residues can be better suppressed. In addition, a conductive layer with excellent compactness and conductivity can be formed. In addition, there is no particular limitation, and the content ratio of the dispersant is approximately 0.01 to 10 parts by mass, typically 0.05 to 5 parts by mass, and preferably 0.1 to 2.7 parts by mass relative to 100 parts by mass of the precious metal powder. Thus, the removability of the unexposed portion and the etching resistance of the exposed portion can be balanced at a high level. That is, the removability of the unexposed portion can be improved in the development process, and the high adhesion (tackiness) to the substrate can be achieved for the exposed portion.
[0072] <Organic Binder>
[0073] The photosensitive composition may further contain an organic binder on the basis of the above-mentioned essential components. The organic binder is a component that improves the adhesion between the substrate and the conductive film (uncured material) before photocuring. As the organic binder, one or more kinds can be appropriately selected from the conventionally known substances, according to, for example, the type of the substrate, the type of the photopolymerizable compound, etc. As the organic binder, it is preferred that it can be easily removed with an aqueous developer in the developing process. For example, when an alkaline aqueous developer is used in the developing process, an alkali-soluble resin, such as the above-mentioned compound having an acidic group, is preferred. Thus, it is easier to remove the unexposed part in the developing process.
[0074] Suitable examples of organic binders include cellulose-based polymers such as methyl cellulose, ethyl cellulose, carboxymethyl cellulose, and hydroxymethyl cellulose, acrylic resins, phenolic resins, alkyd resins, polyvinyl alcohol, and polyvinyl butyral, etc. Among them, cellulose-based polymers are preferred from the viewpoint of easy removal in the development step.
[0075] When the photosensitive composition contains an organic binder, there is no particular limitation, but the ratio of the organic binder to the entire photosensitive composition is generally 0.1 to 20 mass %, typically 0.5 to 10 mass %, for example, 1 to 5 mass %.
[0076] <Organic dispersion medium>
[0077] The photosensitive composition may further contain an organic dispersion medium for dispersing these components in addition to the above-mentioned essential components. The organic dispersion medium is a component that imparts appropriate viscosity and fluidity to the photosensitive composition, improves the operability of the photosensitive composition, or improves the operability when formed into a conductive film. As the organic dispersion medium, one or more kinds of organic dispersion mediums may be appropriately selected from conventionally known substances, for example, according to the type of photopolymerizable compound, and the like.
[0078] As a suitable example of the organic dispersion medium, there can be mentioned alcohol solvents such as pineol, dihydropineol (menthol), TEXANOL, 3-methyl-3-methoxybutanol, benzyl alcohol, etc.; glycol solvents such as ethylene glycol, propylene glycol, diethylene glycol, etc.; ether solvents such as dipropylene glycol methyl ether, methyl cellosolve (ethylene glycol monomethyl ether), cellosolve (ethylene glycol monoethyl ether), butyl carbitol (diethylene glycol monobutyl ether), etc.; ester solvents such as diethylene glycol monobutyl ether acetate, dipropylene glycol methyl ether acetate, butanediol acetate, butyl diglycol acetate, butyl cellosolve acetate, butyl carbitol acetate (diethylene glycol monobutyl ether acetate), isobornyl acetate, etc.; hydrocarbon solvents such as toluene, xylene, naphtha, petroleum hydrocarbons, mineral spirits, and other organic solvents.
[0079] Among them, from the viewpoint of improving the storage stability of the photosensitive composition and the workability during the formation of the conductive film, an organic solvent having a boiling point of 150° C. or higher is preferred, and an organic solvent having a boiling point of 170° C. or higher is more preferred. In addition, as another suitable example, from the viewpoint of suppressing the drying temperature after printing the conductive film to a low level, an organic solvent having a boiling point of 250° C. or lower is preferred, and an organic solvent having a boiling point of 220° C. or lower is more preferred. This can improve productivity and reduce production costs.
[0080] Suitable commercially available organic solvents include, for example, Dawanor DPM (trademark) (boiling point: 190° C., manufactured by Dow Chemical Company), Dawanor DPMA (trademark) (boiling point: 209° C., manufactured by Dow Chemical Company), menthol (boiling point: 207° C.), menthol P (boiling point: 216° C.), Isopar H (boiling point: 176° C., manufactured by Kanto Fuel Co., Ltd.), and SW-1800 (boiling point: 198° C., manufactured by Maruzen Oil Co., Ltd.).
[0081] When the photosensitive composition contains an organic dispersion medium, there is no particular limitation, but the ratio of the organic dispersion medium to the entire photosensitive composition is generally 1 to 50 mass %, typically 3 to 30 mass %, for example, 5 to 20 mass %.
[0082] <Other added ingredients>
[0083] Photosensitive composition can further contain various additives as required on the basis of the above-mentioned components as long as it does not obviously damage the effect of the technology disclosed herein. As additives, one or more than two kinds can be suitably selected from the materials known in the past and used. As an example of additives, for example, inorganic fillers, photosensitizers, inhibitors, free radical scavengers, antioxidants, ultraviolet absorbers, plasticizers, surfactants, leveling agents, thickeners, defoamers, anti-gelling agents, stabilizers, preservatives, pigments, etc. can be cited. It is not particularly limited, and the ratio of additives in the overall photosensitive composition is roughly below 5% by mass, typically below 3% by mass, for example, below 2% by mass, and preferably can be set to below 1% by mass.
[0084] As mentioned above, the photosensitive composition disclosed herein comprises: a solubility parameter as high as 9.9 (cal / cm 3 ) 1 / 2 The above dispersant. Thus, the unexposed portion can be removed quickly and appropriately in the development process. As a result, the development time can be shortened and the generation of residues between lines can be reduced. In other words, the space between adjacent wirings can be stably ensured. Therefore, even a conductive layer of a thin line with a small L / S can be formed with good reproducibility, which can improve productivity and yield rate.
[0085] <Uses of the photosensitive composition>
[0086] According to the photosensitive composition disclosed herein, a conductive layer of a thin line can be stably formed. Therefore, the photosensitive composition disclosed herein can be suitably used for forming a conductive layer in various electronic components such as inductor components, capacitor components, and multilayer circuit boards.
[0087] The electronic components can be variously mounted in various forms such as surface mount type and through-hole mount type. The electronic components can be stacked type, winding type, or thin film type. Typical examples of inductor components include high-frequency filters, common mode filters, inductors (coils) for high-frequency circuits, inductors (coils) for general circuits, high-frequency filters, choke coils, transformers, etc.
[0088] As an example of electronic components, ceramic electronic components can be cited. It should be noted that in this specification, "ceramic electronic components" refers to all electronic components made of ceramic materials, including: all electronic components with amorphous ceramic substrates (glass ceramic substrates) or crystalline (i.e. non-glass) ceramic substrates. As typical examples of ceramic electronic components, there can be cited: high-frequency filters with ceramic substrates, ceramic inductors (coils), ceramic capacitors, low-temperature co-fired ceramic substrates (Low Temperature Co-fired Ceramics Substrate: LTCC substrate), high-temperature co-fired ceramic substrates (High Temperature Co-fired Ceramics Substrate: HTCC substrate), etc.
[0089] In addition, there are no special restrictions on the ceramic material, and examples include oxide materials such as zirconium oxide (zirconia), magnesium oxide (magnesium oxide), aluminum oxide (alumina), silicon oxide (silicon dioxide), titanium oxide (titania), cerium oxide (cerium oxide), yttrium oxide (yttrium oxide), and barium titanate; composite oxide materials such as cordierite, mullite, forsterite, talc, sialon, zircon, and ferrite; nitride materials such as silicon nitride (silicon nitride) and aluminum nitride (aluminum nitride); carbide materials such as silicon carbide (silicon carbide); hydroxide materials such as hydroxyapatite; and the like.
[0090] Figure 1 1 is a cross-sectional view schematically showing the structure of the multilayer chip inductor 1. It should be noted that: Figure 1 The dimensional relationship (length, width, thickness, etc.) in the drawings does not necessarily reflect the actual dimensional relationship. In addition, the symbols X and Y in the drawings represent the left-right direction and the up-down direction, respectively. However, these are just directions for convenience of explanation.
[0091] The multilayer chip inductor 1 includes a main body 10 and external electrodes 20 provided on both side surfaces of the main body 10 in the left-right direction X. The multilayer chip inductor 1 has a size such as 1608 shape (1.6 mm×0.8 mm) or 2520 shape (2.5 mm×2.0 mm).
[0092] The main body 10 has a structure in which a ceramic layer (dielectric layer) 12 and an internal electrode layer 14 are integrated. The ceramic layer 12 is made of a ceramic material. In the vertical direction Y, the internal electrode layer 14 is arranged between the ceramic layers 12. The internal electrode layer 14 is formed using the above-mentioned photosensitive composition. The internal electrode layers 14 adjacent to each other in the vertical direction Y with the ceramic layer 12 sandwiched therebetween are connected by through holes 16 provided in the ceramic layer 12. Thus, the internal electrode layer 14 is configured into a three-dimensional spiral shape (spiral shape). Both ends of the internal electrode layer 14 are connected to the external electrodes 20, respectively.
[0093] Such a multilayer chip inductor 1 can be manufactured, for example, through the following steps.
[0094] That is, first, a paste containing a ceramic material as a raw material, a binder resin and an organic solvent is prepared, and the paste is supplied to a carrier sheet to form a ceramic green sheet. Next, the ceramic green sheet is rolled and cut into a desired size to obtain a plurality of ceramic layer forming green sheets. Next, via holes are appropriately formed at predetermined positions of the plurality of ceramic layer forming green sheets using a puncher or the like.
[0095] Next, the photosensitive composition is used to form a conductive film of a predetermined coil pattern at predetermined positions of a plurality of raw sheets for forming a ceramic layer. As an example, a conductive film in an unfired state can be formed by a manufacturing method including the following steps: (Step S1: Film-forming step) a step of applying a photosensitive composition to a raw sheet for forming a ceramic layer and drying it to form a conductive film formed of a dried body of the photosensitive composition; (Step S2: Exposure step) a step of covering the conductive film with a photomask having a predetermined opening pattern, exposing the conductive film through the photomask, and partially photocuring the conductive film; (Step S3: Development step) a step of etching the photocured conductive film to remove the unexposed portion.
[0096] It should be noted that when the above-mentioned photosensitive composition is used to form a conductive film, a conventionally known method can be appropriately used. For example, in (step S1), the photosensitive composition can be applied using various printing methods such as screen printing, a rod coater, etc. The photosensitive composition can be dried at a temperature below the boiling point of the photopolymerizable compound and the photopolymerization initiator, typically at 50 to 100°C. In (step S2), exposure can be performed using, for example, an exposure machine that emits light in a wavelength range of 10 to 500nm, such as a high-pressure mercury lamp, a metal halide lamp, a xenon lamp, and other ultraviolet irradiation lamps. In (step S3), an alkaline aqueous developer can typically be used for etching. For example, an aqueous solution containing sodium hydroxide, sodium carbonate, etc. can be used. The concentration of the alkaline aqueous solution can be adjusted to, for example, 0.01 to 0.5% by mass.
[0097] Next, (step S4: firing process) a plurality of green sheets for forming a ceramic layer having an unfired conductive film are stacked and pressed together. Thus, a stack of unfired ceramic green sheets is produced. Next, the stack of ceramic green sheets is fired, for example, at 600 to 1000° C. Thus, the ceramic green sheets are sintered together to form a main body 10, which includes: a ceramic layer 12; and an internal electrode layer 14 formed by a fired body of a photosensitive composition. Then, an appropriate external electrode forming paste is applied to both ends of the main body 10 and fired, thereby forming an external electrode 20.
[0098] As described above, the multilayer chip inductor 1 can be manufactured.
[0099] Several embodiments of the present invention will be described below, but the present invention is not intended to be limited to the above embodiments.
[0100] (Preparation of dispersant)
[0101] First, eight types of commercially available dispersants (dispersants a to h) shown below were prepared.
[0102] (Dispersant a): Malialim (trademark) SC1015F manufactured by Daicel Ornex Co., Ltd., a comb-shaped high molecular weight ionic dispersant having a polycarboxylic acid as the main skeleton and polyoxyalkylene chains on the side chains, with a weight average molecular weight of 20,000 to 30,000
[0103] (Dispersant b): Hypermer (trademark) KD-2 manufactured by Croda Japan Ltd., a comb-shaped high molecular weight ionic dispersant having a polyamine as the main skeleton and polyoxyalkylene chains on the side chains, weight average molecular weight 2000
[0104] (Dispersant c): Hypermer (trademark) KD-9 manufactured by Croda Japan Ltd., a comb-shaped high molecular weight ionic dispersant having a polycarboxylic acid as the main skeleton and hydrocarbon chains on the side chains, weight average molecular weight 760, acid value 74 mgKOH / g
[0105] (Dispersant d): Hypermer (trademark) KD-21 manufactured by Croda Japan Ltd., a zwitterionic dispersant containing an amide bond and a carboxyl group
[0106] (Dispersant e): Hypermer (trademark) KD-3 manufactured by Croda Japan Ltd., a comb-shaped high molecular weight ionic dispersant having a polyamine main skeleton and hydrocarbon chains on the side chains
[0107] (Dispersant f): Hypermer (trademark) LP5 manufactured by Croda Japan Ltd., a comb-shaped high molecular weight ionic dispersant having a polyamine main skeleton and hydrocarbon chains on the side chains
[0108] (Dispersant g): Hypermer (trademark) KD-15 manufactured by Croda Japan Ltd., a linear ionic dispersant having oleic acid as the main chain and a dicarboxylic acid at one end of the main chain
[0109] (Dispersant h): Crodafos (trademark) O3A manufactured by Croda Japan Ltd., phosphoric acid-based dispersant
[0110] (Measurement of SP value of dispersant)
[0111] The SP value of each dispersant was calculated by turbidity titration. Specifically, 0.3 g of the dispersant was weighed in a beaker at 25° C., and a 9.8 (cal / cm 3 ) 1 / 2 11.3 ml of acetone (good solvent) was added to dissolve the dispersant completely. A poor solvent with a low SP value (δ ml) of 7.2 (cal / cm 3 ) 1 / 2 The amount of n-hexane added at the point where white turbidity occurs is recorded. Similarly, a poor solvent with a high SP value (δmh) of 23.4 (cal / cm 3 ) 1 / 2 The amount of pure water added was recorded as Vmh (ml) at the point where white turbidity occurred. The results are shown in Table 1 below.
[0112] [Table 1]
[0113] Table 1
[0114]
[0115] Then, the SP values δml and δmh of the poor solvent and the drop amounts Vml and Vmh described in Table 1 were substituted into the following formula (1) to calculate the SP value (δ). The results are shown in Tables 1 and 2. As shown in Tables 1 and 2, the SP value of dispersants a to d alone is 9.9 (cal / cm 3 ) 1 / 2 The SP value of dispersants e to h alone is less than 9.9 (cal / cm 3 ) 1 / 2 .
[0116]
[0117] (Wherein, V ml is the volume of the poor solvent with low SP value, V mh is the volume of the poor solvent with high SP value, δ ml is the SP value of the poor solvent with low SP value, δ mh It is the SP value of the poor solvent with a high SP value. )
[0118] (Preparation of Photosensitive Composition)
[0119] First, prepare silver powder (D 50 In addition, an acrylic polymer (CYCLOMER P (trademark) ACA Z320 manufactured by Daicel Ornex Co., Ltd., weight average molecular weight: 23000, double bond equivalent: 450, resin acid value: 130 mgKOH / g, Tg value: 140° C.) and a urethane acrylate monomer were prepared as photopolymerizable compounds.
[0120] Then, the prepared silver powder, acrylic polymer, urethane acrylate monomer, cellulose-based polymer compound as an organic binder, photosensitizer, photopolymerization initiator (IRGACURE (trademark) 369 manufactured by BASF Japan Ltd.), and other additives (here, anti-gelling agent, polymerization inhibitor and ultraviolet absorber are used) are weighed to give the content ratios shown in Table 2, dissolved in an organic dispersion medium, and further appropriately added with dispersants a to h, thereby preparing photosensitive compositions (Examples 1 to 9, Comparative Examples 1 to 7). It should be noted that the mass ratios shown in Table 2 are the content ratios (parts by mass) when the silver powder is 100 parts by mass.
[0121] (Wiring pattern creation)
[0122] First, apply the prepared photosensitive composition to commercially available ceramic green sheets in a size of □4cm×4cm by screen printing. Then, dry it at 60°C for 15 minutes and form a conductive film (solid film) on the green sheet (film-like body forming process). Next, cover the conductive film with a photomask. At this time, a photomask with a wiring line width of 20μm and a spacing (space) of 20μm (L / S=20μm / 20μm) between adjacent lines is used as the photomask. With the photomask covering the conductive film, use an exposure machine at an illumination of 9mJ / cm 2 、Exposure 1800mJ / cm 2The exposed portion is irradiated with light under conditions of to solidify the exposed portion (exposure process). After exposure, a 0.1 mass % alkaline Na2CO3 aqueous solution (developer) is blown onto the surface of the ceramic green sheet until the development point (BP) is reached (development process). It should be noted that BP is the time until the unexposed portion is developed in a 0.1 mass % alkaline developer and the disappearance of the unexposed portion can be visually confirmed. After removing the unexposed portion in this way, it is washed with pure water and dried at room temperature. In this way, a conductive film (dry film) of a wiring pattern is formed on the ceramic green sheet.
[0123] (Evaluation of Wiring Pattern)
[0124] The wiring patterns prepared above were evaluated for developability, the presence of residues, and tackiness.
[0125] Evaluation of development properties:
[0126] In the above-mentioned development process, the time (development time) until the development point (BP) is reached is measured. The results are shown in the "Development Time (Seconds)" column of Table 2. In addition, the development time of Comparative Example 1 (a test example in which a dispersant is not added) is used as a reference, and for each test example, the difference in development time from Comparative Example 1 is calculated. The results are shown in the "Difference from Comparative Example 1 (Seconds)" column of Table 2. In addition, based on the difference in development time from Comparative Example 1, the developability is evaluated with the following indices.
[0127] “⊚”: The development time is shorter by 5 seconds or more than that in Comparative Example 1 (developability is good).
[0128] "X": The developing time is the same as or slower than that of Comparative Example 1 (poor developing property).
[0129] · Evaluation of the presence or absence of residue:
[0130] The space portion of the wiring pattern was observed with an optical microscope for a total of 10 fields of view, and the presence or absence of residue was confirmed from the obtained observation images. The results are shown in the "Presence or absence of residue" column of Table 2. The description of this column is as follows.
[0131] "◎": Among 10 fields of view, there are residues in less than 1 field of view.
[0132] "○": Among 10 fields of view, 2 to 4 fields of view contained residues.
[0133] “×”: Among 10 fields of view, 5 or more fields of view contained residues.
[0134] Evaluation of stickiness:
[0135] A polyethylene terephthalate (PET) film was placed on the conductive film formed above and pressed from above with a load of 2 kg for 24 hours. Then, the adhesion of the conductive film when the PET film was peeled off after 24 hours was evaluated. The results are shown in the "Adhesion" column of Table 2. The description of this column is as follows.
[0136] "◎": The conductive film was not attached to the PET film (no peeling).
[0137] “×”: The conductive film adheres to the PET film (with peeling).
[0138] [Table 2]
[0139]
[0140] Comparative Example 1 is a test example in which no dispersant was added. As shown in Table 2, in Comparative Example 1, the development time was relatively long, and a large amount of residue was confirmed in the space portion. In addition, Comparative Examples 3 to 7 using a dispersant having an SP value of 9.46 or less also had a long development time as in Comparative Example 1, and a large amount of residue was confirmed in the space portion. Furthermore, in Comparative Example 2 using a dispersant having an SP value of 9.80, the development time was shorter than that in Comparative Example 1, but a large amount of residue was still confirmed in the space portion.
[0141] For Comparative Examples 1 to 7, the SP value was 9.9 (cal / cm 3 ) 1 / 2 In Examples 1 to 9 of the above dispersants, the development time is short compared to Comparative Example 1, and the generation of residues is also suppressed to a low level. In other words, by using a dispersant having an SP value of 9.9 or more, the effect of the technology disclosed herein is exerted without exception, for example, regardless of the structure of the dispersant. Among them, in Examples 1 to 8 that do not contain compounds having an SP value lower than 9.9, the generation of residues is more well suppressed. In addition, by comparing Examples 1 to 5 with different amounts of dispersant added, by making the content ratio of the dispersant to 100 parts by mass of silver powder 0.1 to 2.7 parts by mass, the removability of the unexposed portion can be improved in the development process, and the adhesion (viscosity) of the exposed portion to the substrate is improved. These results show the significance of the technology disclosed herein.
[0142] As mentioned above, although this invention was demonstrated in detail, these are only examples, and this invention can be variously modified in the range which does not deviate from the summary.
Claims
1. A photosensitive composition comprising: a noble metal powder, a photopolymerizable compound, a photopolymerization initiator and a dispersant, The solubility parameter of the dispersant is 9.9 (cal / cm 3 ) 1 / 2 above, The dispersant is a linear straight-chain type or a comb-shaped structure in which a plurality of side chains are arranged along a linear main skeleton, and contains one or more compounds having an acidic group.
2. The photosensitive composition according to claim 1, wherein The photopolymerizable compound includes a photopolymerizable polymer having a weight average molecular weight of 5,000 or more.
3. The photosensitive composition according to claim 1 or 2, wherein The photopolymerizable compound includes one or more compounds having an acidic group.
4. The photosensitive composition according to claim 1 or 2, wherein The content ratio of the dispersant is 0.1 parts by mass or more and 2.7 parts by mass or less, based on 100 parts by mass of the entire precious metal powder.
5. The photosensitive composition according to claim 1 or 2, wherein The dispersant is composed only of a solubility parameter of 9.9 (cal / cm 3 ) 1 / 2 The above compounds are composed.
6. The photosensitive composition according to claim 1 or 2, wherein The precious metal powder includes silver-based particles.
7. A composite comprising: green sheets; and A conductive film is disposed on the green sheet and is formed from a dried product of the photosensitive composition according to any one of claims 1 to 6. 8 . An electronic component comprising: a conductive layer formed from a calcined body of the photosensitive composition according to claim 1 .
9. A method for producing an electronic component, comprising the steps of applying the photosensitive composition according to any one of claims 1 to 6 to a substrate, exposing and developing the composition, and then baking the composition to form a conductive layer consisting of a baked body of the photosensitive composition.
Citation Information
Patent Citations
Black photosensitive resin composition, black matrix, color filter, liquid crystal display device, and organic electroluminescence display device
JP2015161815A
Carbon conductive material slurry
JP2018045820A
Photosensitive electroconductive paste, electroconductive thin film, magnetic circuit, and touch panel
WO2015040908A1